1992
DOI: 10.2166/wst.1992.0345
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Nature of the By-Products Formed and the Risks of Toxicity when Disinfecting a Secondary Effluent with Ozone

Abstract: Among the disinfection processes of urban waste water, ozonation and UV irradiation are fast gathering interest. To avoid what happened with chlorine it is necessary to have a look at the formation of by-products and the risks of toxicity when such processes are used. We were already working on this type of problem in 1984, although we did not make a point of communicating in extenso the results obtained during a 2-year period of pilot plant and laboratory studies at La Roche sur Yon (Vendée, France). The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
9

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
10
2
9
Order By: Relevance
“…These beneficial effects of ozone application in WW on chlorophyll-a are in accordance with Escher et al (2009), who reported increased growth rates of Pseudokirchneriella subcapitata when exposed to ozone treated WW samples. The study by Escher et al (2009) and the present study differ from that by Langlais et al (1992), who observed a growth inhibition of the green algae Scenedesmus subspicatus following exposure to ozone treated WW. Langlais et al (1992) hypothesised that biologically available dissolved organic substances were partially destroyed, which limited nutrient availability and, ultimately, reduced algal growth.…”
Section: Effects On Algaecontrasting
confidence: 99%
See 1 more Smart Citation
“…These beneficial effects of ozone application in WW on chlorophyll-a are in accordance with Escher et al (2009), who reported increased growth rates of Pseudokirchneriella subcapitata when exposed to ozone treated WW samples. The study by Escher et al (2009) and the present study differ from that by Langlais et al (1992), who observed a growth inhibition of the green algae Scenedesmus subspicatus following exposure to ozone treated WW. Langlais et al (1992) hypothesised that biologically available dissolved organic substances were partially destroyed, which limited nutrient availability and, ultimately, reduced algal growth.…”
Section: Effects On Algaecontrasting
confidence: 99%
“…The study by Escher et al (2009) and the present study differ from that by Langlais et al (1992), who observed a growth inhibition of the green algae Scenedesmus subspicatus following exposure to ozone treated WW. Langlais et al (1992) hypothesised that biologically available dissolved organic substances were partially destroyed, which limited nutrient availability and, ultimately, reduced algal growth. But transformation products also might have adversely affected algal growth, as they can be more toxic than their parent compounds (e.g., Li et al 2008;Zouboulis et al 2008).…”
Section: Effects On Algaecontrasting
confidence: 99%
“…Studies show that ozone treatments are able to reduce COD, BOD, pH, colour, turbidity, SS and TOC (Total Organic Carbon) (Gardiner and Montgomery 1968;Nebel et al 1973;Paraskeva et al 1998;Alfafara et al 2000) as well as aromatic compounds, unsaturated fatty acids, anionic detergents, amino acids and polysaccharides (Langlais et al 1992), trihalomethanes and organic halides (Amirsardari et al 2001). Then, it is more advantageous the use of ozone than chlorine, since studies (Fatta-Kassinos et al 2010) show their presence in treated wastewaters after chlorine treatment.…”
Section: State Of the Artmentioning
confidence: 99%
“…OH) que é gerado pela decomposição do ozônio. No entanto, um inconveniente muitas vezes encontrado nos estudos de degradação com ozônio refere-se ao aumento da toxicidade de alguns intermediários de reação 58,61 , o que torna necessário o acompanhamento do processo através de testes de toxicidade.…”
Section: Oxidação Indiretaunclassified